Non-invasive myocardial work: an echocardiographic measure of post-infarct scar on contrast-enhanced cardiac magnetic resonance imaging. (25th November 2020) - El Mahdiui, M; Van Der Bijl, P; Abou, R; De Lustosa, R.P; Van Der Geest, R; Ajmone Marsan, N; Delgado, V; Bax, J.J
Abstract: Background: Late gadolinium contrast enhanced cardiac magnetic resonance (LGE CMR) imaging accurately quantifies the extent of fibrosis and transmurality in chronically infarcted left ventricular (LV) segments, and identifies viability. Moreover, CMR characterizes the remote, non-infarcted zone, which is an emerging region of interest following ST-segment elevation myocardial infarction (STEMI). Non-invasive myocardial work is a novel LV function parameter - calculated from speckle-tracking strain echocardiography and sphygmomanometrically-determined blood pressure, which has shown excellent correlation with invasively measured myocardial work. Purpose: To explore the relation of non-invasively estimated parameters of LV myocardial work to post-infarct scar on LGE CMR, and to compare myocardial work indices between the infarct core and remote zone in STEMI patients who were treated with primary percutaneous coronary intervention (PCI). Methods: Patients with a STEMI who underwent primary PCI and LGE CMR, in addition to echocardiographic studies where non-invasive myocardial work analysis was feasible, were included. The LV was subdivided into non-infarcted, non-transmural and transmurally infarcted segments. The remote zone was defined as the non-infarcted myocardial segment diametrically opposed to the infarct core, without any evidence of LGE. Myocardial work indices were compared with linear mixed models, ANOVA and Wilcoxon signed rank tests. Results: 53 patients (89% male, age 58±9 years) and 689 segments were analysed. The mean scar burden comprised 14±7% of the total LV mass and 76 (11%) segments showed transmural LGE. The following non-invasive myocardial work indices: myocardial work index (MWI), constructive work (CW) and myocardial work efficiency (MWE) showed a significant inverse relationship with infarct transmurality (p<0.05 for all comparisons) while a positive trend was observed for wasted work (WW) (p=0.086) (Figure 1). The core zone demonstrated lesser MWI (1237±568 vs. 1514±518 mmHg%; p=0.010), CW (1331±627 vs. 1827±537 mmHg%; p<0.001) and MWE (92 (84–98) vs. 98 (95–99) %; p<0.001) as well as greater WW when compared to the remote zone (107 (26–196) vs. 26 (10–90) mmHg%; p=0.001). Conclusions: In STEMI patients who underwent primary PCI, MWI, CW and MWE were significantly related to the extent of transmural infarction, while WW demonstrated a trend. MWI, CW and MWE were significantly lower, and WW higher, in the core zone compared to the remote zone. Non-invasive myocardial work indices may provide an echocardiographic method for determining post-infarct viability, as well as characterization of the remote zone. Funding Acknowledgement: Type of funding source: None